1975
DOI: 10.1136/hrt.37.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propranolol on left ventricular function, segmental wall motion, and diastolic pressure-volume relation in man.

Abstract: Precise quantitation of the effects of the non-selective beta adrenergic blocking drug propranolol (O.I5 mg/kg body weight) on left ventricularfunction, segmental wall motion, and diastolic pressure-volume relation in man has been performed. High fidelity left ventricular pressure measurements and simultaneous single-plane angiocardiograms were recorded on a video disc and volumes calculated by a light-pen computer system. Systolic segmental wall motion was computer analysed using the long axis-quadrasection m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 9 publications
2
20
1
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This study sought to characterize the alterations in performance of the heart in delivering an increased stroke volume and in diastolic filling during stress and how these parameters of left ventricular performance might be altered by ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This study sought to characterize the alterations in performance of the heart in delivering an increased stroke volume and in diastolic filling during stress and how these parameters of left ventricular performance might be altered by ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…3 Diastolic performance has been demonstrated to be very sensitive to ischemia. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Careful assessment of diastolic properties during stress, however, has not been previously well characterized by radionuclide angiography, and might prove to enhance the sensitivity of detection of ischemia. We therefore sought to evaluate and characterize the detection of ischemic heart disease by alteration in diastolic as well as systolic parameters during exercise.…”
mentioning
confidence: 99%
“…This direct action of filling pressure provides the mechanism by which agents that increase blood pressure shift the pressurevolume curve up 10 and agents that drop blood pressure drop it. 10 " 13 In particular, Alderman and Glantz 10 showed that angiotensin not only increased left ventricular enddiastolic pressure and aortic pressure, but also right ventricular pressure; nitroprusside dropped all three. Shirato et al 87 showed, in dogs, that shifts in the diastolic pressure-diameter curve with nitroprusside only occur with the pericardium closed.…”
Section: Ventricular Interaction and The Pericardiummentioning
confidence: 99%
“…For example, propranolol administration resulted in decreased heart rate, elevated blood pressure, and reduced pulmonary artery pressure, while phenylephrine administration resulted in elevated blood pressure, decreased heart rate, and increased cardiac output, and saline volume loading resulted in increased cardiac output and elevated blood pressure. Effects of propranolol: Previous studies have suggested that catecholamineinduced LVOT in the context of ACS resulted from compensative hyperkinesis of the nonischemic LVOT and the inferoposterior segment [1][2][3][4][5] and that the negative inotropic effect of propranolol can attenuate the enhanced hyperdynamic motion of the nonischemic LV segments 9) and thereby result in reversal of LVOT obstruction. 6) Further, reversal of LVOT obstruction may induce a paradoxical increase in cardiac output and systemic blood pressure and thereby decrease diastolic LV filling pressure and pulmonary artery pressure.…”
Section: Discussionmentioning
confidence: 99%